(untitled) (Voice of Teacher, 2025)
The spark of conflict begins from the epicenter and spreads causing numerous episodes of conflict. Conventional approaches like negotiation, mediation and judicial settlement to conflict resolution are guided by the spirit of essentialism. They are monodimentional. Visualizing the big picture of conflict, multidimensional approaches like preventive diplomacy, humanitarian intervention and reconciliation and truth have been developed to address the roots of conflict for constructive transformation. These new approaches are far more progressive and effective than the conventional ones. The time has come to rethink about our approaches to conflict resolution and transformation. This paper delves into the three issues: episodes of conflict, conventional methods of conflict resolution and the need to address the root causes (epicenters) of conflict. The objectives of the paper are to describe the episodes of conflict, to analyze various conventional methods of conflict resolution, and to explore why conflict transformation is important. This paper follows the qualitative method. Firstly, a survey of various theories of conflict and approaches has been carried out. Then, conventional approaches have been evaluated. Finally, the reasons to address the epicenters of conflict have been explored. The findings are without addressing the epicenters of conflict, conflict transformation is not possible. Without conflict transformation, we cannot think of constructive change. In order to study the life cycle of conflict, we have to move from the episode to its epicenter (root-cause). This episodic view of conflict is the new approach to the study of conflict.